Taeumjowi-tang, a Traditional Korean Sasang Remedy, Improves Obesity-Atopic Dermatitis Comorbidity by Regulating Hypoxia-Inducible Factor 1 Alpha - Park, Jinbong; Youn, Dong-Hyun; Kang, JongWook; Ahn, Kwang Seok; Kwak, Hyun Jeong; Um, Jae-Young (Frontiers in Pharmacology, 2019)
Atopic dermatitis (AD) is an inflammatory disease of the skin, resulting from an immune dysfunction, that often occurs as a comorbidity of obesity. This investigation evaluated the capacity of Taeumjowi-tang (TJT), a Korean herbal formulation from the Sasang medical tradition to influence prognostic features of AD and obesity in a mouse model. Here, obesity and AD were induced by a high-fat diet (HFD) and 1-fluoro-2,4-dinitrobenzene (DNFB). Following an 8-week HFD regimen and 4 weeks of DNFB administration, the comorbid (CO) group manifested increased body weight and AD-like lesions, as compared to normal control (NC) mice, while TJT administration diminished these symptoms of obesity and AD. Specifically, TJT treatment reduced epidermal thickness and eosinophil/mast cell infiltration, along with reduction in immunoglobulin E, interleukin (IL)-4, IL-6 and tumor necrosis factor-alpha (TNF-α). It was additionally demonstrated that TJT suppresses HFD/DNFB-associated increase of the inflammation-related nuclear factor-kappa beta (NF-κB) and mitogen activated protein kinase. Moreover, significantly increased levels of hypoxia inducible factor-1 alpha (HIF-1α) protein was observed in CO group versus controls, an increase significantly down-regulated by TJT-treatment. These outcomes suggest that TJT may prove useful in clinical management of obesity-AD comorbidity treatment, an effect that may be due to regulation of HIF-1α expression.